2020
DOI: 10.1002/jat.4020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico genetic toxicity screening of flavor compounds and other ingredients in tobacco products with emphasis on ENDS

Abstract: Electronic nicotine delivery systems (ENDS) are regulated tobacco products and often contain flavor compounds. Given the concern of increased use and the appeal of ENDS by young people, evaluating the potential of flavors to induce DNA damage is important for health hazard identification. In this study, alternative methods were used as prioritization tools to study the genotoxic mode of action (MoA) of 150 flavor compounds. In particular, clastogen-sensitive (γH2AX and p53) and aneugensensitive (p-H3 and polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Currently, there are over 15,000 different e-liquid flavors on the market [ 33 ]. The Flavor and Extract Manufacturers Association (FEMA) has identified over 1000 flavorings commonly used in e-liquids that may pose a respiratory hazard due to possible volatility and irritant properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are over 15,000 different e-liquid flavors on the market [ 33 ]. The Flavor and Extract Manufacturers Association (FEMA) has identified over 1000 flavorings commonly used in e-liquids that may pose a respiratory hazard due to possible volatility and irritant properties.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies have identified that aliphatic aldehydes (in fruity flavors), aromatic aldehydes (in sweet and spicy flavors), and non-phenolic terpenes (floral and citric flavors) generate more lung damage [ 34 , 35 , 36 ]. Another study identified two cinnamaldehyde flavor compounds, ethyl maltol, maltol, and propylene glycol, found in the flavors, as potentially genotoxic [ 33 ]. E-liquid without nicotine produced high levels of carbonyl [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such predictive methods are time- and resource- efficient compared to conventional in vitro and in vivo testing methods . Recently, FDA-CTP applied computational methods to assess the ability of tobacco flavor chemicals to form DNA adducts and to assess genotoxic and mutagenic potential. , Computational methods can be used as a science-based approach to search for functional groups or “structural alerts” that contribute to the chemical’s reactivity. These structural alerts commonly include Michael acceptors, acylating and alkylating agents, aldehydes and ketones, cyanates and cyanides, and thioesters. Computational methods can be used to identify generalized chemical substructures of toxicological concern for the toxicity end points .…”
Section: Introductionmentioning
confidence: 99%
“…12 Recently, FDA-CTP applied computational methods to assess the ability of tobacco flavor chemicals to form DNA adducts 13 and to assess genotoxic and mutagenic potential. 14,15 Computational methods can be used as a science-based approach to search for functional groups or "structural alerts" that contribute to the chemical's reactivity. 16−18 These structural alerts commonly include Michael acceptors, acylating and alkylating agents, aldehydes and ketones, cyanates and cyanides, and thioesters.…”
Section: ■ Introductionmentioning
confidence: 99%